What is a parked bicycle? Vehicle fleet characteristics in Australia. (September 2020) - Napper, Robbie
Abstract: Bicycle parking facilities are an important part of the transport system and their design can make bicycle transport more convenient. At a detailed level, the design of bicycle parking devices depends on how they relate to the bicycle's properties. This research seeks to provide a more detailed understanding of the characteristics and fleet of bicycles to inform better policy and practice. Set in Australia, an urbanised country aiming to increase a presently low bicycle mode share, the results are potentially useful to other low bicycle mode share cultures. Visual analysis reveals that although the relevant Australian standard describes a spatial envelope for bicycles, the envelope introduces a treatment of bicycle geometry at odds with vehicle characteristics; namely the contradiction that the spatial envelope in the standard significantly over states the volume of a bicycle, while at the same time the handlebars of the bicycle are inadequately accommodated. A random sample of 180 parked bicycles in Australian urban environments provides a detailed geometry database and shows that the Australian bicycle fleet is heterogeneous around clusters of geometry reflecting industry standards, but does not match with the spatial envelope provided in the standard. Photographic observations of these bicycles provide an insight into bicycle characteristics and parking behaviours, in particular revealing that 55% of the sample bicycles were not equipped with kick stands and thus depend on parking infrastructure for stability. Evidence from the field suggests that some bicycle users are willing to park bicycles more closely than suggested in the standard. Highlights: Provides detailed analysis of bicycle geometry for the development of bicycle parking devices Visual analysis reveals deficiencies in treating bicycle envelope as a rectangular prism. The parked bicycle population is heterogeneous and exceeds the spatial envelope of the relevant local standard. User behaviour is observed to be at odds with bicycle parking system described in the relevant local standard.